The Ncar East in the 21st Century - Ritter, Wigand (Promet - Traffic&Transportation, 2012)
Although an ’avalanche of people’ may be expected in thenear future lillie confidence seems to be justified with respect toa peaceful and prosperous development in the Near East. Politicalantagonism, often fuelled by religious intolerance threatei!Sor even pre1·ents the evaluation of promising opportunities atthis huge area between the Old World continents which couldotlwwise benefit so much from the by-passing great world trafficroutes.